2007
DOI: 10.1038/sj.onc.1210860
|View full text |Cite
|
Sign up to set email alerts
|

Snail is a repressor of RKIP transcription in metastatic prostate cancer cells

Abstract: Diminished expression of the metastasis suppressor protein RKIP was previously reported in a number of cancers. The underlying mechanism remains unknown. Here, we show that the expression of RKIP negatively correlates with that of Snail zinc-transcriptional repressor, a key modulator of normal and neoplastic epithelial-mesenchymal transition (EMT) program. With a combination of loss-of-function and gain-of-function approaches, we showed that Snail repressed the expression of RKIP in metastatic prostate cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
191
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(204 citation statements)
references
References 32 publications
10
191
1
1
Order By: Relevance
“…[28][29][30][31] Snail and RKIP expression levels are inversely correlated in prostate cancer cell lines and patient's samples. 25 Snail and RKIP have also shown opposite effects in the regulation of tumor cell resistance to apoptotic stimuli. and activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[28][29][30][31] Snail and RKIP expression levels are inversely correlated in prostate cancer cell lines and patient's samples. 25 Snail and RKIP have also shown opposite effects in the regulation of tumor cell resistance to apoptotic stimuli. and activity.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Besides E-cadherin, Snail was recently shown to repress the transcription of another tumor suppressor gene product, namely Raf-1 kinase inhibitor protein (RKIP). 25 RKIP is a member of the phosphatidylethanolamine-binding proteins (PEBP) family and among its main functions RKIP inhibits both the NFκB and MAPK signaling pathways. RKIP mediates its inhibitory activity on NFκB and MAPK through physical association with Raf-1 and TAK/NIK and IKK kinases, respectively, leading to inhibition of their activities as kinases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a Merkel carcinoma line was identified that overexpressed RKIP and lost ERK signaling; however, further studies revealed that RKIP depletion did not rescue the ERK signaling defect consistent with RKIP's role as a modulator rather than suppressor of the MAPK pathway [34]. Finally, a recent study showed that Snail, a mediator of the epithelial-mesenchymal transition (EMT), can inhibit RKIP transcription and negatively correlates with RKIP levels in tumors, consistent with a role for RKIP in metastasis [35]. Since RKIP expression is decreased during progression in a variety of cancers, it is likely that RKIP affects a fundamental step in the process rather than targeting tumor-specific mechanisms of invasion or colonization.…”
mentioning
confidence: 96%
“…Mechanisms including gene methylation and transcriptional repression by the epithelial-mesenchymal transition (EMT)-promoting factor, SNAIL, have been implicated in rkip gene regulation in other types of cancers. 80,81 Another important issue is to identify the molecular basis of RKIP's effects on tumor malignancy, invasion, and metastasis. Are the signaling pathways that are known to be influenced by RKIP involved?…”
Section: Rkip and Association With Brain Cancermentioning
confidence: 99%